Applied developmental psychology : theory, practice, and research from Japan - Shwalb, David W.; Nakazawa, Jun; Shwalb, Barbara J. (Advances in applied developmental psychology series (Information Age Pub.), 2005)
This volume provides an overview of recent research on child development in Japan. Sixteen contributions from leading psychologists cover such topics as the development of manga (comic book) literacy, the study of mathematics in school, and the effects of job- related temporary father absence.